Poverty Alleviation Strategy: Challenges and Opportunities in Realizing SDGs in Indonesia - Marta Ayu Saputri,; Millah, Mazida Nurul; Reza Nurul Falah,; Siska Afiyati Dewi, (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The poverty rate in Indonesia reaches 24.06 million people out of a total population of 280 million. Various influencing factors include, for example, the still low quality of education. This study discusses the challenges, opportunities, and strategies for poverty alleviation in Indonesia within the context of achieving the Sustainable Development Goals (SDGs), particularly the first goal: "No Poverty." The research method used is descriptive qualitative with a literature review approach, analyzing secondary data from various sources. The findings indicate that the main challenges include unequal access to education, healthcare services, and employment opportunities. Opportunities lie in the development and utilization of technology. Meanwhile, the strategies that can be implemented include improving the quality of services such as education and infrastructure, conducting social assistance programs, economic empowerment, and targeted social aid distribution. Keywords: SDGs, poverty, Challenge, Opportunity, Strategy